Core-shell structured semiconducting PMMA/polyaniline snowman-like anisotropic microparticles and their electrorheology - Liu, Ying Dan (Langmuir : the ACS journal of surfaces and colloids, 2010)
Core-shell structured semiconducting snowman-like particles were synthesized, and their electrorheological (ER) characteristics under an applied electric field were examined. Monodispersed snowman-like poly(methyl methacrylate) (PMMA) particles were fabricated previously using a seed emulsion polymerization procedure. These anisotropic particle-based ER fluids, which were tested using a rotational rheometer, exhibited unusual ER properties in the flow curves at various electric field strengths when analyzed using the Cho-Choi-Jhon model. The dielectric spectra, as supporting data for the ER effect, were measured using a LCR meter. The relaxation time of the ER fluid was relatively shorter than typical ER fluids